Pacific communications : weaving the technological and social fabric - Pacific Telecommunications Council Conference (12th : 1990 : Honolulu, Hawaii); Wedemeyer, Dan J.; Lofstrom, Mark D.; Pacific Telecommunications Council (Honolulu : Pacific Telecommunications Council, 1990)
13